FPGA implementation of new LM-SPIHT colored image compression with reduced complexity and low memory requirement compatible for 5G - Yasmine M. Tabra; Bayan Mahdi Sabbar (International Journal of Reconfigurable and Embedded Systems (IJRES), 2019)
The revolution in 5G mobile systems require changes to how image is handled. These changes are represented by the required processing time, the amount of space for uploading and downloading. In this paper, a development on WT (Wavelet Transform) along with LM-SPIHT (Listless-Modified Set Partitioning in Hierarchical tree) coding and with additional level of Runlength encoding for image compression has been proposed. The new implementation reduces the amount of data needed to be stored in several stages, also the amount of time required for processing. The compression has been implemented using VHDL (Very High Descriptive Language) on netFPGA-1G-CLM Kintex-7 board. The new implementation results show a reduction in the complexity as processing time.